2013
DOI: 10.4161/hv.26886
|View full text |Cite
|
Sign up to set email alerts
|

Medical and economic burden of influenza in the elderly population in central and eastern European countries

Abstract: Influenza affects 5–15% of the population during an epidemic. In Western Europe, vaccination of at-risk groups forms the cornerstone of influenza prevention. However, vaccination coverage of the elderly (>65 y) is often low in Central and Eastern Europe (CEE); potentially because a paucity of country-specific data limits evidence-based policy making. Therefore the medical and economic burden of influenza were estimated in elderly populations in the Czech Republic, Hungary, Kazakhstan, Poland, Romania, and Ukra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 37 publications
4
35
0
12
Order By: Relevance
“…Our study of the direct medical costs of laboratory-confirmed influenza hospitalizations in patients aged 65 y in Spain found the mean cost per case was € 3,219, higher than the € 2,490 found in Poland, 14 the € 1,570.3 found in China, 27 or the € 1,270€ (in terms of 2011 purchasing power) reported in Italy. 28 The reduction in cost of 2.5% in vaccinated cases in our study came mainly from the reduction in the ICU stay, sparing mechanical ventilation and preventing secondary bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our study of the direct medical costs of laboratory-confirmed influenza hospitalizations in patients aged 65 y in Spain found the mean cost per case was € 3,219, higher than the € 2,490 found in Poland, 14 the € 1,570.3 found in China, 27 or the € 1,270€ (in terms of 2011 purchasing power) reported in Italy. 28 The reduction in cost of 2.5% in vaccinated cases in our study came mainly from the reduction in the ICU stay, sparing mechanical ventilation and preventing secondary bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 82%
“…Reports estimating costs have shown differences between countries, although the magnitude of the economic burden due to influenza excess hospitalizations is of great relevance everywhere. 10,[14][15][16] The aim of this study was to determine the costs associated with laboratory-confirmed influenza-related hospitalization in patients aged 65 y and assess the effect of influenza immunization in reducing costs due to hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…While some estimates of the national burden of influenza are available for countries of the WHO European Region, the majority of primary study estimates come from Western Europe and no estimates are available for over half of the member states 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Except for a study on the economic influenza burden among the elderly in 6 middle‐income countries of Central and Eastern Europe in 2010/11,9 influenza burden in the Romanian population has never been estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Molinari et al (2007) estimated that the total financial burden of the seasonal influenza infection in the US amounts to $10.4 billion a year and that the older population is responsible for 64 % of the total economic burden. It has been estimated that direct costs of influenza in the elderly population in Poland can be very high (Kovacs et al 2014). Therefore, efforts to reduce the disease's burden in the elderly population would have a substantial influence on the costs of seasonal influenza (Ryan et al 2006).…”
Section: Introductionmentioning
confidence: 99%